1943
DOI: 10.1172/jci101418
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of the Serum and Plasma Proteins by Salt Precipitation in Infants and Children. 1. The Changes With Maturity and Age. 2. The Changes in Glomerulonephritis. 3. The Changes in Nephrosis1

Abstract: The various components constituting the plasma protein complex have been characterized by many different chemical methods. Perhaps the most extensively used method of defining the component proteins has been by describing their solubility behavior in salt solutions. Thus, the terms fibrinogen, euglobulin, pseudoglobulin, and albumin have been applied, not to molecular species or chemical entities, but to the fractional parts of the total plasma protein complex, separated by precipitation at specified salt conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
0

Year Published

1945
1945
1974
1974

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…The globulin levels were relatively lower as a percentage of the full-term infants' levels than the albumin levels. These low levels confirm the observations made by Darrow and Cary (1933) and by Rapoport, Rubin, and Chaffee (1943). Other previous observers (Utheim, 1920;Bridge, Cohen, and McNair Scott, 1941;Hickmans, Finch, and Tonks, 1943) have found that the serum protein levels of premature infants are lower than those of full-term infants in the early weeks of life, but few details regarding the weight at birth and none about the diet of the infants are given in their reports.…”
Section: Resultssupporting
confidence: 78%
“…The globulin levels were relatively lower as a percentage of the full-term infants' levels than the albumin levels. These low levels confirm the observations made by Darrow and Cary (1933) and by Rapoport, Rubin, and Chaffee (1943). Other previous observers (Utheim, 1920;Bridge, Cohen, and McNair Scott, 1941;Hickmans, Finch, and Tonks, 1943) have found that the serum protein levels of premature infants are lower than those of full-term infants in the early weeks of life, but few details regarding the weight at birth and none about the diet of the infants are given in their reports.…”
Section: Resultssupporting
confidence: 78%
“…2.--Average serum protein levels in present series compared with the levels obtained by Trevorrow et al(1941),Darrow and Cary (1933),and Rapoport et al (1943)…”
supporting
confidence: 48%
“…The electrophoretic method yields the additional information that the concentration distribution of the individual globulins is quite different in the two types of material. Although poor in total globulin, the fetal samples are relatively rich in the presumably antibody-containing y globulin, the fetal values of P,/PG, 2 Although there is some evidence (15) that the solubility of the a, component corresponds to that of an albumin, it has been classified here as a globulin. When this component was first reported (6), the author did not state explicitly that it was a globulin but the terminology he suggested implied that he considered it to belong in this class of proteins.…”
Section: Discussionmentioning
confidence: 95%